Characterization of a quasi-sinusoidal transmission grating without membrane substrate in the 200–1500 eV photon energy regions. Issue 3 (4th February 2016) - Wang, Chuanke; Wang, Baoqing; Yi, Tao; Fan, Quanping; Kuang, Longyu; Li, Jin; Li, Tingshuai; Zhu, Xiaoli; Liu, Shenye; Jiang, Gang
Abstract : A 1000-line/mm quasi-sinusoidal transmission grating (QSTG) without membrane substrate has been designed and fabricated, which is utilized to eliminate the higher order diffraction for soft X-ray spectrum measurement in the experiments of inertial confinement fusion. The grating was calibrated using an X-ray beam on synchrotron radiation facility. It shows that the QSTG has the desired diffraction property and the higher order diffraction components are efficiently suppressed in the photon energy ranges from 200 to 1500 eV.